2015
DOI: 10.1007/s10876-015-0848-z
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study of Molecular Hydrogen Adsorption on Small Gold–Copper Binary Clusters

Abstract: Density functional theory calculations were performed to investigate the molecular adsorption behaviors of hydrogen on small bimetallic Au n Cu m clusters with n ? m B 5. H 2 prefers to bind to a copper atom in Au n Cu m H 2 complexes when both Au and Cu sites co-exist. The adsorption energies of Au n H 2 are larger than Cu n H 2 clusters with the same n and the adsorption energies of bimetallic cluster hydrides are between those of mono Au n H 2 and Cu n H 2 . The adsorption of H 2 on Au n Cu m can enhance th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 39 publications
9
11
0
Order By: Relevance
“…In the case of bimetallic clusters, mixing Cu and Au preserves the rhombic structure of the four-atom cluster. The positions of the Cu and Au atoms in the rhombus as the composition changes are in full agreement with the structures predicted by Zhao et al On the other hand, starting with Pt 4 and replacing Pt by Cu atoms preserves the three-dimensional (tetrahedral) structure in Cu 1 Pt 3 and Cu 2 Pt 2 , but the structure of Cu 3 Pt 1 is nearly a rhombus with a small deviation from planarity. Apparently, the differences in the structural trends of Cu–Au and Cu–Pt bimetallic clusters are related to the differences in the electronic configuration of Au and Pt atoms, the latter having a d shell incompletely filled.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…In the case of bimetallic clusters, mixing Cu and Au preserves the rhombic structure of the four-atom cluster. The positions of the Cu and Au atoms in the rhombus as the composition changes are in full agreement with the structures predicted by Zhao et al On the other hand, starting with Pt 4 and replacing Pt by Cu atoms preserves the three-dimensional (tetrahedral) structure in Cu 1 Pt 3 and Cu 2 Pt 2 , but the structure of Cu 3 Pt 1 is nearly a rhombus with a small deviation from planarity. Apparently, the differences in the structural trends of Cu–Au and Cu–Pt bimetallic clusters are related to the differences in the electronic configuration of Au and Pt atoms, the latter having a d shell incompletely filled.…”
Section: Resultssupporting
confidence: 87%
“…Both Cu 4 and Au 4 are predicted to have planar rhombic structures, in agreement with previous work. , Au 4 has been studied by Ghiringhelli and co-workers using DFT and dispersion corrections. The structures of the ground state (rhombus) and the first low-lying isomer (Y-shape) are reproduced by our calculations.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Doping commonly used hydrogenation or dehydrogenation catalysts, such as Ni, Pd, Pt, with another metal has been found to be beneficial in fine-tuning catalytic activity, e.g., by lowering the H-H bond activation barrier. 2 Nevertheless, studies exploring the reasons for why mixed metal catalysts are better than single metal ones are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…2 A density functional theory study observed that the adsorption of H 2 on Au n Cu m clusters enhanced the stability of the whole cluster. 4 A comparative study of CH 3 OH dehydrogenation on Pt 7 versus Pt 5 Ni 2 found that charge transfer from Ni to Pt increased the electron density on the platinum atoms' 5d orbital, thereby improving the catalytic activity of the Pt 5 Ni 2 cluster relative to Pt 7 . 5 More recently, we reported that the mixed metal hydride cluster anion, PtZnH 5 À , has a planar five-coordinated structure and unusual stability owing to its s-aromaticity.…”
Section: Introductionmentioning
confidence: 99%